Helpful or Harmful? The Role of Personality Traits in Student Experiences of the COVID-19 Crisis and School Closure. (November 2022) - Iterbeke, Kaat; De Witte, Kristof
Little is known about the individual differences in student experiences and expectations of the COVID-19 crisis and the resulting school closures. Yet, as the crisis may have uniquely impacted students, knowledge about their personalities is highly relevant. In a sample of 347 Flemish students, this study explored the association between personality traits and differences in responses to the crisis. The Big Five personality traits of students were assessed in January 2020, prior to the COVID-19 outbreak. Students were reassessed in June 2020 with a set of items related to well-being, remote learning, and family and social life. The results suggested that more conscientious students (showing a better perception of remote learning) and more open students (considering the period as an opportunity to learn new skills) adjusted well to the changes induced by the crisis. On the contrary, students high in neuroticism (showing higher stress levels) were harmed.